Picture this: Photographers no better than controls for recognizing unfamiliar faces. (August 2022) - Baker, Kristen A.; Mondloch, Catherine J.
With the exception of super recognizers and forensic examiners, people make a surprising number of errors when deciding whether photographs of unfamiliar faces belong to the same person or different people. Training protocols designed to improve professionals' (e.g., passport officers) performance often include photography. We evaluated the influence of life-time photography experience on the ability to distinguish matched versus mismatched face pairs. Expert photographers were not more sensitive to identity than hobbyists or novices—despite specializing in human subjects; Hobbyists were more liberal (more same responses) than Experts. We conclude that photography experience is not a route to expertise.